Carvedilol inhibits cADPR- and IP3-induced Ca2+ release - Morgan, A; Bampali, K; Ruas, M; Factor, C; Back, T; Chen, S; Galione, A (American Scientific Publishers, 2017)
Spontaneous Ca2+ waves, also termed store-overload-induced Ca2+ release (SOICR), in cardiac cells can trigger ventricular arrhythmias especially in failing hearts. SOICR occurs when Ryanodine receptors (RyRs) are activated by an increase in sarcoplasmic reticulum (SR) luminal Ca2+. Carvedilol is one of the most effective drugs for preventing arrhythmias in patients with heart failure. Furthermore, carvedilol analogues with minimal β-blocking activity also block SOICR showing that SOICR-inhibiting activity is distinct from that for β-block. We show here that carvedilol is a potent inhibitor of cADPR-induced Ca2+ release in sea urchin egg homogenate. In addition, the carvedilol analog VK-II-86 with minimal β-blocking activity also suppresses cADPR-induced Ca2+ release. Carvedilol appeared to be a non-competitive antagonist of cADPR and could also suppress Ca2+ release by caffeine. These results are consistent with cADPR releasing Ca2+ in sea urchin eggs by sensitizing RyRs to Ca2+ involving a luminal Ca2+ activation mechanism. In addition to action on the RyR, we also observed inhibition of inositol 1,4,5-trisphosphate (IP3)-induced Ca2+ release by carvedilol suggesting a common mechanism between these evolutionarily related and conserved Ca2+ release channels.